2021
DOI: 10.1097/aln.0000000000003898
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Risks of Dexamethasone in Noncardiac Surgery

Abstract: Dexamethasone is an effective antiemetic and improves patient quality of recovery. Meta-analyses and a recent large trial found no increase in risk of surgical site infection. Dexamethasone should be more widely used in perioperative practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…and P.D.P.). In the absence of an accepted definition of abdominal surgery and given the variety of different types of procedures included in prior investigations, [39][40][41][42] we selected a broad range of procedures performed within the abdomen, excluding transplant, trauma, obstetrics, and endoscopic procedures. We limited our study sample to cases that were manually reviewed for reporting to the National Surgical Quality Improvement Program (NSQIP), to ensure standardized ascertainment of postoperative complications.…”
Section: Cohort Identificationmentioning
confidence: 99%
“…and P.D.P.). In the absence of an accepted definition of abdominal surgery and given the variety of different types of procedures included in prior investigations, [39][40][41][42] we selected a broad range of procedures performed within the abdomen, excluding transplant, trauma, obstetrics, and endoscopic procedures. We limited our study sample to cases that were manually reviewed for reporting to the National Surgical Quality Improvement Program (NSQIP), to ensure standardized ascertainment of postoperative complications.…”
Section: Cohort Identificationmentioning
confidence: 99%
“… 9 10 11 12 The potential analgesic effects of glucocorticoids as an adjuvant are probably due to their anti-inflammatory properties, including suppression of proinflammatory cytokines and induction of anti-inflammatory cytokines, reduction of prostaglandin synthesis, and with possible lowering of the excitability of nerve cells. 13 14 …”
Section: Introductionmentioning
confidence: 99%
“…49,50 Dexamethasone given intravenously has also been shown to prolong regional block, and has an added benefit of providing excellent long-lasting prophylaxis for postoperative nausea and vomiting. [51][52][53][54] In addition, recent studies have shown that IV dexamethasone reduces break through pain reported with single shot blocks. 55 In regard to aesthetic plastic surgery applications, prolonged steroid use causes delayed wound healing, increased surgical site infections, and hyperglycemia.…”
Section: Steroidsmentioning
confidence: 99%